Global anisotropic FWI - Debens,HA; Warner,MR; Umpleby,A (2015)
Seismic anisotropy influences both the kinematics and dynamics of seismic waveforms. As such, if not taken into account properly during multi-parameter full-waveform seismic inversion (FWI), the anisotropy can manifest itself as significant error in the recovered P-wave velocity model. With this in mind we demonstrate a hybrid local-global inversion scheme to extract the low-wavenumber component of the anisotropy in combination with a high-resolution P-wave velocity model. This can then be followed by conventional local inversion for one or both parameters. Our results demonstrate that this technique suppresses the cross-talk between anisotropy and velocity, whilst producing more accurate final models for both parameters.